Strategi Penguatan Ekonomi Nasional di Tengah Kenaikan Pajak - Yessica Amelia; Ngadi Permana; Farah Qalbia (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
The increase in the Value Added Tax (VAT) rate from 11% to 12% which will be enforced starting January 2025 is part of the tax reform efforts aimed at increasing state revenues and strengthening the foundation of national development. It is estimated that this policy can generate additional revenues of up to IDR 150 trillion per year, which will be used to fulfill strategic sectors such as infrastructure, education, health, and poverty alleviation programs. However, this policy also raises concerns about its negative impacts, such as decreased purchasing power, increased inflation, and pressure on the sustainability of micro, small, and medium enterprises (MSMEs). Therefore, this study aims to examine strategies for strengthening the national economy through a comprehensive approach, including providing tax incentives to MSMEs, subsidies for basic needs, strengthening social assistance, and increasing transparency in managing the state budget in order to mitigate the impact of the policy fairly and sustainably.